# Translating a Sentence Into a One-Step Equation Online Quiz

Following quiz provides Multiple Choice Questions (MCQs) related to Translating a Sentence Into a One-Step Equation. You will have to read all the given answers and click over the correct answer. If you are not sure about the answer then you can check the answer using Show Answer button. You can use Next Quiz button to check new set of questions in the quiz. Q 1 - Express the following sentence into a one-step equation.

(Hint: Use x as the unknown number)

Six times a number minus 3 equals 75

A - 8x – 3 = 75

B - 6x – 3 = 75

C - 6x – 3 = 72

D - 6x – 4 = 75

### Explanation

Step 1:

Let the number be x.

Step 2:

Six times the number = 6x

Six times a number minus 3 = 6x – 3

Step 3:

Therefore, 'Six times a number minus 3 equals 75' translated into one-step equation is

6x – 3 = 75

Q 2 - Express the following sentence into a one-step equation.

(Hint: Use x as the unknown number)

Twelve less than 4 times a number is 52

A - 4x – 12 = 51

B - 4x – 13 = 52

C - 4x – 12 = 52

D - 4x + 12 = 52

### Explanation

Step 1:

Let the number be x.

Step 2:

4 times the number is 4x.
Since 'less' means subtraction, twelve less than 4 times the number = 4x – 12

Step 3:

'Is' means equals to

Therefore,'Twelve less than 4 times a number is 52' translated into one-step equation is

4x – 12 = 52

Q 3 - Express the following sentence into a one-step equation.

(Hint: Use x as the unknown number)

The difference of thrice a number and 9 is 6

A - 3x – 6 = 9

B - 3x – 9 = 7

C - 3x + 9 = 6

D - 3x – 9 = 6

### Explanation

Step 1:

Let the number be x.

Step 2:

Thrice the number = 3x

Since difference means subtraction, the difference of thrice a number and 9 = 3x – 9

Step 3:

'Is' means equals to

Therefore, 'The difference of thrice a number and 9 is 6' translated into one-step equation is

3x – 9 = 6

Q 4 - Express the following sentence into a one-step equation.

(Hint: Use x as the unknown number)

The sum of 24 and thrice a number is 57

A - 24 − 3x = 57

B - 24 + 3x = 57

C - 24 ÷ 3x = 57

D - 24 + 2x = 57

### Explanation

Step 1:

Let the number be x.

Step 2:

Thrice the number = 3x

Since sum means addition, the sum of 24 and thrice a number = 24 + 3x

Step 3:

Therefore, 'The sum of 24 and thrice a number is 57' translated into one-step equation is

24 + 3x = 57

Q 5 - Express the following sentence into a one-step equation.

(Hint: Use x as the unknown number)

Eleven times a number less 9 is 68

A - 11x – 9 = 68

B - 11x – 9 = 67

C - 11x ÷ 9 = 68

D - 11x + 9 = 68

### Explanation

Step 1:

Let the number be x.

Step 2:

Eleven times the number = 11x

'Less' means subtraction, so eleven times a number less 9 = 11x – 9

Step 3:

Therefore, 'Eleven times a number less 9 is 68' translated into one-step equation is

11x – 9 = 68

Q 6 - Express the following sentence into a one-step equation.

(Hint: Use x as the unknown number)

A number minus 8 is 15

A - x – 7 = 15

B - x – 8 = 14

C - x – 8 = 15

D - x + 8 = 15

### Explanation

Step 1:

Let the number be x.

Step 2:

The number minus 8 = x – 8

Step 3:

'Is' means equal to

Therefore, 'A number minus 8 is 15' translated into one-step equation is

x – 8 = 15

Q 7 - Express the following sentence into a one-step equation.

(Hint: Use x as the unknown number)

5 more than 2 times a number is 17

A - 2x + 7 = 15

B - 2x − 5 = 17

C - 2x ÷ 5 = 17

D - 2x + 5 = 17

### Explanation

Step 1:

Let the number be x.

Step 2:

2 times the number = 2x

More means addition. So, 5 more than 2 times the number = 2x + 5

Step 3:

'Is' means equal to

Therefore, '5 more than 2 times a number is 17'

translated into one-step equation is

2x + 5 = 17

Q 8 - Express the following sentence into a one-step equation.

x(Hint: Use x as the unknown number)

A number increased by 9 is 13

A - x + 8 = 13

B - x + 9 = 13

C - x + 9 = 12

D - x + 9 = 15

### Explanation

Step 1:

Let the number be x.

Step 2:

Increase means addition. So, the number increased by 9 = x + 9

Step 3:

'Is' means equal to

Therefore, 'A number increased by 9 is 13' translated into one-step equation is

x + 9 = 13

Q 9 - Express the following sentence into a one-step equation.

(Hint: Use x as the unknown number)

Ten times a number added to 7 is 27.

A - 10x + 7 = 27

B - 10x + 8 = 27

C - 10x ÷ 7 = 27

D - 10x − 7 = 27

### Explanation

Step 1:

Let the number be x.

Step 2:

Ten times the number = 10x

Ten times the number added to 7 = 10x + 7

Step 3:

'Is' means equal to

Therefore, 'Ten times a number added to 7 is 27'

translated into one-step equation is

10x + 7 = 27

Q 10 - Express the following sentence into a one-step equation.

(Hint: Use x as the unknown number)

The sum of 29 and a number is 37

A - x + 29 = 38

B - x + 27 = 39

C - x + 29 = 37

D - x − 29 = 37

### Explanation

Step 1:

Let the number be x.

Step 2:

Sum means addition. So, the sum of 29 and the number = 29 + x

Step 3:

'Is' means equal to

Therefore, 'The sum of 29 and a number is 37' translated into one-step equation is

29 + x = 37

translating_sentence_into_one_step_equation.htm